Pretreatment of sugarcane bagasse by OX-B to enhancing the enzymatic hydrolysis for ethanol fermentation - da Siva Martins, Luiza Helena; Komesu, Andrea; Moreira Neto, João; de Oliveira, Johnatt Allan Rocha; Rabelo, Sarita Cândida [UNESP]; da Costa, Aline Carvalho (Wiley, 2021)
The main by-product of the alcohol industry is the sugarcane bagasse, which can be used to produce second generation ethanol. Studies about pretreatment technologies are increasingly greater, a fundamental step for the efficient this fuel production. The reagents and wastewater treatment costs are still a bottleneck for this type of technology. The present work aimed to study the pretreatments of sugarcane bagasse using a highly oxidative solution Ox-B. In this study we used high solids loadings, aimed at reducing the use of reagent and the water consumption. We carried out an experimental design 32 for the pretreatment step. The pretreated material followed an enzymatic hydrolysis with 10% (m/v) loading, and enzymatic loading of 15 Filter Paper Units (FPU)/g and 25 cellobiose units (CBU)/g of bagasse. For the best pretreatment condition the desirability tool showed the best pretreatment condition for the release of glucose as 20% solids, 25°C and 2 h, achieving 251.94 mg of glucose per gram of raw bagasse. However, the maximum ethanol yield was 70%, that possible was affected by the presence of chlorine in the pre-treated mass that has been affected the fermentation process. In general, Ox-B proved to be a potential pretreatment agent for sugarcane bagasse. Practical Applications: Sugarcane bagasse is a residual material which can be used for second-generation (2G) bioethanol production. In this study, Ox–B pretreatment of sugarcane bagasse using high solid loadings, both in the pretreatment (20–40% w/v) and the enzymatic hydrolysis (10–20% w/v) stages was conducted in order to reduce reagent usage and consumption of water. The studies will be useful for ethanol production from lignocellulose.